Analisis Pengaruh Grade Jalan terhadap Fuel Consumption pada Kegiatan Overburden Removal Bulan Agustus 2017 di PT Mifa Bersaudara, Meulaboh, Aceh Barat. - Tiara Mentari Nafsya; T. Andika Rama Putra; Teuku Zulfikar (Journal of Geosciences, Mining Engineering, and Technology, 2022)
The fuel ratio target at PT. Mifa Bersaudara has been determined. The ratio is the comparison between the equipments fuel consumption in overnurden removal operation from the loading location to the dumping location to be 0,875 Litre/ Bcm. However, it was found that the actual fuel ratio in June and July 2017 was 1,4 Litre/ Bcm and 1,3 Litre/ Bcm which higher than the target ratio. Observation in the field showed that the greater the grade, the more fuel being consumed by the trucks. The highest calculation of road grade on LP3-DP2 lane was 10% and the highest fuel consumption in LP3-DP2 lane for CAT 773E and CAT 775F were 56,5 litre/hours and 62,2 litre/hours respectively.